1981
DOI: 10.1093/infdis/143.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Plasmid Mediating Resistance to Multiple Antimicrobial Agents During a Prolonged Epidemic of Nosocomial Infections

Abstract: At the Vanderbilt University Medical Center, Nashville, Tennessee, resistance to gentamicin was encountered with increasing frequency among several species of gram-negative bacilli between 1973 and 1977. Representative strains were screened for plasmid DNA content using agarose gel electrophoresis. In strains of Pseudomonas aeruginosa and Serrati marcescens isolated early in the outbreak, gentamicin resistance was mediated by a common 9.8-megadalton nonconjugative plasmid. Either an 80- or a 100-megadalton tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

1982
1982
1995
1995

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…It has previously been shown that determinants for AAC(3) enzymes are transposable (Nugent & Datta, 1980;Rubens et al, 1981) and there are indications that the genes for AAC(3)I and AAC(3)III are related (Rubens et al, 1981). Thus it is interesting to ask whether AAC(3)III and AAC(3)IV are related.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that determinants for AAC(3) enzymes are transposable (Nugent & Datta, 1980;Rubens et al, 1981) and there are indications that the genes for AAC(3)I and AAC(3)III are related (Rubens et al, 1981). Thus it is interesting to ask whether AAC(3)III and AAC(3)IV are related.…”
Section: Discussionmentioning
confidence: 99%
“…It permits plasmids to be allocated to one of a limited number of groups but does not resolve small differences between related plasmids. Therefore, to investigate further our collection of trimethoprim R-plasmids and examine aspects of their epidemiology, we used restriction endonuclease analysis of plasmid DNA, a method that has become widely used for the study of plasmid and bacterial epidemiology (Rubens et al 1981;O'Brien et al 1982;Lyon et al 1984;Beul et al 1985;Platt, Chesham & Kristinsson, 1986). In this study, we applied a simple fingerprinting strategy to investigate the similarities and differences between trimethoprim resistance plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this approach has been widely used to study the epidemiology of both plasmids and their host bacteria (Beul et al 1985;Lyon et al 1984; O'Brien et al 1982;Platt, Chesham & Kristinsson, 1986;Rubens et al 1981). The information provided by the application of these techniques is particularly useful for the study of genera for which no established typing scheme is available (Hawkey, Bennett & Hawkey, 1984) and the investigation of cryptic plasmids (Callihan, Young & Clark, 1983).…”
Section: Introductionmentioning
confidence: 99%